AN UPDATED CHECKLIST AND COMMENTS FOR SECTION PIQUETIA (CAMELLIA, THEACEAE) - Roman Vasilyevich Doudkin; Van Duy Nong; Kim Cong Vu; Thai Vinh Tran; Nie Bing H’Yon; Thi Tham Dang; Van Hoi Quach (Tạp chí Khoa học Đại học Đà Lạt)
New Camellia species in section Piquetia have recently been discovered. It is necessary to enumerate the number of species and update the specific characteristics of this section. Based on the study of more than 30 pieces of literature and a large number of specimens, a total of 15 species belonging to section Piquetia, including two new species, are identified. A taxonomic key to all species is provided, and typical characteristics of the section are also discussed. Information on the distribution, ecology, and conservation status of each species, as well as notes on the differences between closely related species, is also provided.